(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Ruxandra Iordache analyzes Christopher Hampton’s film Imagining Argentina through the lens of the Orpheus myth. Set during Argentina’s military dictatorship, the study explores Carlos’s search for kidnapped wife, Cecilia, his modern Eurydice. Unlike the original myth, Carlos is compelled to look back, using memory and imagination to resist state-imposed amnesia. Ultimately, Iordache argues that art and collective memory function as liberating forces, transforming historical trauma into a vital struggle for truth, justice, and human resilience. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.